Early and late administration of MnTE-2-PyP5+ in mitigation and treatment of radiation-induced lung damage - Gauter-Fleckenstein, Benjamin; Fleckenstein, Katharina; Owzar, Kouros; Jiang, Chen; Rebouças, Júlio S.; Batinic-Haberle, Ines; Vujaskovic, Zeljko (Free radical biology and medicine, 2010)
Chronic production of reactive oxygen and nitrogen species is an underlying mechanism of irradiation (IR)-induced lung injury. The purpose of this study was to determine the optimum time of delivery of an antioxidant and redox-modulating Mn porphyrin, MnTE-2-PyP5+, to mitigate and/or treat IR-induced lung damage. Female Fischer-344 rats were irradiated to their right hemithorax (28 Gy). Irradiated animals were treated with PBS or MnTE-2-PyP5+ (6 mg /kg/24 h) delivered for 2 weeks by sc-implanted osmotic pumps (beginning after 2, 6, 12, 24, or 72 h or 8 weeks). Animals were sacrificed 10 weeks post-IR. Endpoints were body weight, breathing frequency, histopathology, and immunohistochemistry (8-OHdG, ED-1, TGF-β, HIF-1α, VEGF A). A significant radioprotective effect on functional injury, measured by breathing frequency, was observed for all animals treated with MnTE-2-PyP5+. Treatment with MnTE-2-PyP5+ starting 2, 6, and 12 h but not after 24 or 72 h resulted in a significant decrease in immunostaining for 8-OHdG, HIF-1α, TGF-β, and VEGF A. A significant decrease in HIF-1α, TGF-β, and VEGF A, as well as an overall reduction in lung damage (histopathology), was observed in animals beginning treatment at the time of fully developed lung injury (8 weeks post-IR). The catalytic manganese porphyrin antioxidant and modulator of redox-based signaling pathways MnTE-2-PyP5+ mitigates radiation-induced lung injury when given within the first 12 h after IR. More importantly, this is the first study to demonstrate that MnTE-2-PyP5+ can reverse overall lung damage when started at the time of established lung injury 8 weeks post-IR. The radioprotective effects are presumably mediated through its ability both to suppress oxidative stress and to decrease activation of key transcription factors and proangiogenic and profibrogenic cytokines.